2012
DOI: 10.1002/pmic.201100495
|View full text |Cite
|
Sign up to set email alerts
|

A guideline to proteome‐wide α‐helical membrane protein topology predictions

Abstract: For current state‐of‐the‐art methods, the prediction of correct topology of membrane proteins has been reported to be above 80%. However, this performance has only been observed in small and possibly biased data sets obtained from protein structures or biochemical assays. Here, we test a number of topology predictors on an “unseen” set of proteins of known structure and also on four “genome‐scale” data sets, including one recent large set of experimentally validated human membrane proteins with glycosylated si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 48 publications
1
32
0
1
Order By: Relevance
“…HEK293 Cells-The membrane topology of VKORC1L1 was predicted using ten different topology prediction programs (38). Seven out of the ten programs predict four TMDs in VKORC1L1.…”
Section: Determination Of the Membrane Topology Of Vkorc1l1 Inmentioning
confidence: 99%
“…HEK293 Cells-The membrane topology of VKORC1L1 was predicted using ten different topology prediction programs (38). Seven out of the ten programs predict four TMDs in VKORC1L1.…”
Section: Determination Of the Membrane Topology Of Vkorc1l1 Inmentioning
confidence: 99%
“…A guideline to proteome-wide α-helical membrane protein topology has been published recently [29] giving the opportunity to compare the PMIscale predictions with 18 algorithms on control datasets. We compared PMIscale on two benchmark datasets extracted from this work that permit evaluation of membrane-inserted proteins.…”
Section: Resultsmentioning
confidence: 99%
“…The first dataset is composed of cytosolic proteins without any signal peptide or TM segment. For this dataset, the PMIscale based predictor predicts 2.8% proteins with at least one TM segment which places it as one of the three best methods, 12% better than the average performance of the evaluated programs in [29]. The second dataset is composed of extracellular proteins that contain a signal peptide but no TM segment.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the support vector machine program MEMSAT-SVM, which was trained on structurally derived topology data and sequence profiles, achieved~90 % accuracy on a set of experimentally determined membrane protein structures (Nugent and Jones 2009). A recent study comprehensively evaluated the performance of topology prediction methods on various sets including a set of 103 newly determined atomic structures (Tsirigos et al 2012). This analysis indicated that the best performance is obtained by TOPCONS (Bernsel et al 2009), a consensus method that combines five other prediction methods (e.g., SCAMPI (Bernsel et al 2008)) and that the best method for distinguishing membrane from non-membrane proteins is the Hidden Markov Model (HMM)-based method Phobius (Kall et al 2005).…”
Section: Template Identification and Target-template Alignmentmentioning
confidence: 99%